2014
DOI: 10.1152/ajprenal.00036.2014
|View full text |Cite
|
Sign up to set email alerts
|

OMA1 mediates OPA1 proteolysis and mitochondrial fragmentation in experimental models of ischemic kidney injury

Abstract: Acute kidney injury (AKI) is associated with mitochondrial fragmentation, which contributes to mitochondrial damage and tubular cell apoptosis. Mitochondrial fragmentation involves the cleavage of both mitochondrial outer and inner membranes. Cleavage of the outer membrane results from Drp-1-mediated fission activation and Bak-promoted fusion arrest, but the molecular mechanism of inner membrane cleavage remains elusive. OMA1-mediated proteolysis of OPA1, a key inner membrane fusion protein, was recently sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 36 publications
7
85
0
Order By: Relevance
“…Remarkably, when L-OPA1 was genetically preserved by the additional deletion of Oma1, tissue atrophy was reduced in both models and this correlated with a significant improvement in fitness and prolonged lifespan. In another study, Oma1-knockout mice were shown to have improved renal function after ischemic kidney injury, an acute insult that also promotes OPA1 processing (Xiao et al, 2014). These reports therefore demonstrate that the suppression of OMA1 is protective in pathological models that are caused by persistent mitochondrial stress.…”
Section: Mitochondrial-dysfunction-induced Opa1 Processing Causes Celmentioning
confidence: 78%
“…Remarkably, when L-OPA1 was genetically preserved by the additional deletion of Oma1, tissue atrophy was reduced in both models and this correlated with a significant improvement in fitness and prolonged lifespan. In another study, Oma1-knockout mice were shown to have improved renal function after ischemic kidney injury, an acute insult that also promotes OPA1 processing (Xiao et al, 2014). These reports therefore demonstrate that the suppression of OMA1 is protective in pathological models that are caused by persistent mitochondrial stress.…”
Section: Mitochondrial-dysfunction-induced Opa1 Processing Causes Celmentioning
confidence: 78%
“…[1][2][3] Excessive oxidative stress, apoptosis, epithelial and endothelial cell dysfunction, and inflammation are among the important pathophysiologic mechanisms during ischemic AKI. [4][5][6][7] Recent work demonstrates an important pathophysiologic role for T lymphocytes in AKI, but the underlying mechanisms are poorly understood. [8][9][10][11] Traditional mechanisms of immune activation and responses through allo-or self-antigen are not known to occur during AKI.…”
mentioning
confidence: 99%
“…Loss of OMA1 protects cultured cells against apoptosis (Head et al, 2009;Quirós et al, 2012;Jiang et al, 2014;Xiao et al, 2014). We have previously described that apoptosis contributes to neuronal loss in Phb2 NKO mice, but have detected only a limited number of TUN EL-positive neurons (Merkwirth et al, 2012).…”
Section: Oma1 Deletion Protects Phb2-deficient Cells Against Apoptosismentioning
confidence: 99%
“…Oma1-deficient mice exhibit impaired thermogenesis and diet-induced obesity (Quirós et al, 2012). Moreover, loss of OMA1 in cultured cells was found to protect against apoptosis (Head et al, 2009;Quirós et al, 2012;Jiang et al, 2014;Xiao et al, 2014). However, the general in vivo relevance of stress-induced OPA1 processing by OMA1, and in particular its importance for neuronal survival, is not understood.…”
Section: Introductionmentioning
confidence: 99%